2021
DOI: 10.2196/17023
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Mobile Ecological Momentary Assessment of Self-Reported Health-Related Behaviors and Psychological Constructs in Adults: Systematic Review and Meta-analysis

Abstract: Background Mobile ecological momentary assessment (mEMA) permits real-time capture of self-reported participant behaviors and perceptual experiences. Reporting of mEMA protocols and compliance has been identified as problematic within systematic reviews of children, youth, and specific clinical populations of adults. Objective This study aimed to describe the use of mEMA for self-reported behaviors and psychological constructs, mEMA protocol and complia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 121 publications
(167 reference statements)
10
69
3
Order By: Relevance
“…As alternatives, it would have been necessary to either allow user-initiated prompts (i.e., whenever there currently is a social interaction) or to assess social interactions much more frequently (e.g., every 30 min). However, both approaches did not seem viable because they would have come with increased participant burden and possibly a reduced compliance (Williams et al 2021 ). In addition, it would not be feasible for participants to report on their interactions during their everyday life routines in such a high frequency and, most importantly, the reporting itself could have interfered with social interactions (e.g., by interrupting conversations), thereby reducing ecological validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alternatives, it would have been necessary to either allow user-initiated prompts (i.e., whenever there currently is a social interaction) or to assess social interactions much more frequently (e.g., every 30 min). However, both approaches did not seem viable because they would have come with increased participant burden and possibly a reduced compliance (Williams et al 2021 ). In addition, it would not be feasible for participants to report on their interactions during their everyday life routines in such a high frequency and, most importantly, the reporting itself could have interfered with social interactions (e.g., by interrupting conversations), thereby reducing ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…In case of cross-level interactions, the predictor on the higher level was interpreted as moderator (Andersson et al 2014). Interaction plots were built using the R packages 'effects' (Fox and Weisberg 2019) and 'ggplot2' (Wickham 2016).…”
Section: Moderation Analyses: Testing the Stress-buffering Hypothesismentioning
confidence: 99%
“…Compared with other ESM studies, this compliance rate is relatively low, as meta-analyses have shown completion rates of 82% to 85% [ 38 , 39 ]. However, comparing data with other ESM studies is difficult because the absence of methodological guidelines related to the use of this method has resulted in a large heterogeneity of designs [ 39 ], and compliance rates have not been reported in approximately half of the studies [ 40 ]. For better compliance, fewer study days, less assessments per day, and fewer items per assessment are advised [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, comparing data with other ESM studies is difficult because the absence of methodological guidelines related to the use of this method has resulted in a large heterogeneity of designs [ 39 ], and compliance rates have not been reported in approximately half of the studies [ 40 ]. For better compliance, fewer study days, less assessments per day, and fewer items per assessment are advised [ 38 , 40 ]. In addition, as previous ESM studies recommend at least 3 completed questionnaires per day for a reliable analysis, which occurred consistently only during the first week of this study, we recommend using the ESM for a maximum of 7 days [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only if compliance is high, one is able to generalize the answers to daily life and data analysis are sufficiently powered. In most studies, participants answer on average 50–95% of all ESM surveys ( Wen et al, 2017 ; van Roekel et al, 2019 ; Williams et al, 2021 ). As a rule of thumb, 70–80% compliance indicates good data quality.…”
Section: Practical Step-by-step Guidementioning
confidence: 99%